2018
DOI: 10.7163/eu21.2018.35.5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial planning determinants of cohesion policy implementation in Polish regions

Abstract: The main objective of the paper is to present directions of mutual interrelationships between the state of spatial planning (at different levels of public administration) and effective cohesion policy, conceived as operational programmes carried out in Poland in the years 2004-2016. In the research study, the following results were attained: defining the basic planning conditions of development policies implementation resulting from integration with EU, indicating the consequences of these conditions for terri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The source of these assumptions was the knowledge about the problems in the field of water and space management in the selected research area, resulting from the analyzed conditions [58][59][60][61][62][63] and the knowledge of the spatial planning system in Poland with its weaknesses [20][21][22][23][24]64]. So, it resulted both from the authors' own research and from the studied scientific literature, cited above, and the confirmation of these assumptions is as follows:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The source of these assumptions was the knowledge about the problems in the field of water and space management in the selected research area, resulting from the analyzed conditions [58][59][60][61][62][63] and the knowledge of the spatial planning system in Poland with its weaknesses [20][21][22][23][24]64]. So, it resulted both from the authors' own research and from the studied scientific literature, cited above, and the confirmation of these assumptions is as follows:…”
Section: Methodsmentioning
confidence: 99%
“…These systems are so liberal or unintegrated that in fact they lead to "planned chaos" [20]. Among other places, in Poland, the key problem is the lack of effective shaping and protection of the spatial order with the help of the available tools of spatial policy [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The abovementioned research allowed for determining the distribution of funds allocated to possible water supply and sewerage investment in rural areas among individual voivodships. The regional demand for water supply investment varies significantly, which should be taken into account when planning the regional distribution of funds within the Cohesion Policy (Komornicki et al, 2018;Berkowitz, Monfort, and Pieńkowski, 2019).…”
Section: Technical Infrastructurementioning
confidence: 99%
“…Another problem is the lack of adequate local enforcement capacity and the constant regulations changes. This applies, inter alia, to Poland, where the critical problem is the lack of effective planning using available spatial policy tools [23,[82][83][84]. Research has also shown that many binding plans include regulations inconsistent with applicable law and inadequate to current needs, which clearly proves the system's weakness.…”
Section: Threats and Opportunities For The Implementation Of Local Spatial Plan Regulations On Resmentioning
confidence: 99%